THE BIRDS OF THE KANGEAN ISLANDS AND AN APPRAISAL OF THEIR CONSERVATION STATUS - Berryman, Alex J; Rutt, Cameron L; Irham, Mohammad; Balen, Sebastianus (Bas) van (Treubia, 2024)
The Kangean islands are a biologically poorly known archipelago situated in the Java Sea, Indonesia, approximately 120 km directly north of Bali. These islands host an avifauna comprising at least 13 endemic subspecies, two of which have by some sources recently been considered species. We combine historical published literature with our own surveys of the archipelago in 2007–2008, 2010 and 2023 to produce a complete list of the islands’ birds (n=140 species) and their distribution across the islands. We evaluate in more detail the conservation status of all endemic taxa, as well as several others we consider to be of concern. Despite its listing as Vulnerable on the IUCN Red List, the endemic Kangean Tit-babbler Mixornis prillwitzi is highly tolerant of habitat degradation and is among the islands’ least threatened birds. However, because of trapping, the archipelago’s endemic taxon of Red-breasted Parakeet Psittacula alexandri kangeanensis, and its populations of Green Junglefowl Gallus varius and Common Hill Myna Gracula religiosa are likely at risk of extirpation. The endemic taxon of White-rumped Shama Copsychus malabaricus, sometimes afforded species rank as ‘Kangean Shama’ C. nigricauda, may already be (at least functionally) extinct in the main archipelago. We recommend longer and more detailed surveys of the islands’ birds, and that an effective protected area is established on main Kangean island, which hosts the largest area of remaining forest in the archipelago and most of its endemic taxa.